Peran Posyandu Dalam Memantau Pertumbuhan Dan Perkembangan Balita - Sri Rahayu; Dena Nur Rahmatika (Jurnal Ilmiah Kesehatan, 2022)
Abstract Health development can increase awareness, ability and willingness to live a healthy life that will realize optimal public health status. A mother's assumption about posyandu as a place to weigh is not to monitor her child's growth and development. The mother's assumption is due to lack of knowledge about the function of the posyandu so that the growth and development of toddlers is not monitored. This study was to determine the knowledge and attitudes of mothers of children under five about the growth and development of children under five at the posyandu. This type of correlation research uses a cross sectional design, carried out in June-July 2022 at Poyandu RW 5, Bongsari Village, Semarang City. The population is mothers who have children under five aged 1-5 years as many as 250 respondents and the sample is 65 respondents. The sampling technique used was purposive sampling. The results show that respondents with less knowledge level are 31 respondents (47.7%); and poor attitude as many as 37 respondents (56.9%); it is known that p value = 0.001 means that there is a relationship between knowledge and attitudes of mothers of children under five about growth and development of children under five in posyandu RW 5, Bongsari sub-district, Semarang City; Suggestions to the community, especially mothers who have toddlers, are expected to always be active and visit the posyandu so that the growth and development of their toddlers is monitored Keywords: Knowledge, Attitude, Active Visit Abstrak Pembangunan kesehatan dapat meningkatkan kesadaran, kemampuan dan kemauan untuk hidup sehat akan mewujudkan derajat kesehatan masyarakat yang optimal. Asumsi seorang ibu tentang posyandu sebagai tempat menimbang bukan untuk memantau tumbuh kembang anaknya. Anggapan ibu tersebut dikarenakan pengetahuan yang kurang tentang fungsi posyandu sehingga tumbuh kembang balitanya kurang terpantau. Penelitian ini untuk mengetahui pengetahuan dan sikap ibu balita tentang pertumbuhan dan perkembangan balita di posyandu. Jenis penelitian korelasi menggunakan rancangan cross sectional, dilaksanakan pada bulan Juni-Juli 2022 di Poyandu RW 5 Kelurahan Bongsari kota Semarang. Populasinya ibu yang memiliki anak balita usia 1-5 tahun sebanyak 250 responden dan sampelnya 65 responden. Teknik sampling yang digunakan purposive sampling. Hasilnya menunjukan bahwa responden dengan tingkat pengetahuannya kurang sebanyak 31 responden (47.7%); dan sikapnya kurang sebanyak 37 responden (56.9%); diketahui p value=0.001 berarti bahwa ada hubungan antara pengetahuan dan sikap ibu balita tentang pertumbuhan dan perkembangan balita di posyandu RW 5 kelurahan Bongsari Kota Semarang; Saran pada masyarakat khususnya ibu yang mempunyai balita diharapkan selalu aktif dan berkunjung ke posyandu agar tumbuh kembang balitanya terpantau. Kata Kunci : Pengetahuan, Sikap, Keaktifan Kunjungan